The Impact of ‘No Work, No Pay’ Policy on Industrial Actions: A Case Study of ASUU at the University of Lagos - Oluwabusayo Olanrewaju Oni; Mariam Gbajumo-Sheriff (Master of Management, School of Business and Management, Petra Christian University, 2025)
Trade unions regard the right to strike as a vital tool to counter low wages or unfavorable working conditions. This study explores the impact of the